(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to the issues of improving the technical and tactical training of student wrestlers, and it reveals the specific aspects of the formation of complex technical and tactical movements of wrestlers.